Effect of Filtration Process on Oxidative Stability and Minor Compounds of the Cold-Pressed Hempseed Oil during Storage - Vincenzo Lo Turco; Federica Litrenta; Vincenzo Nava; Ambrogina Albergamo; Rossana Rando; Giovanni Bartolomeo; Angela Giorgia Potortì; Giuseppa Di Bella (MDPI AG, 2023)
Cold-pressed hempseed oil (HO) has been increasingly exploited in the human diet for its excellent nutritional and healthy properties. However, it has a high content of polyunsaturated fatty acids (PUFAs) and chlorophylls, which inevitably accelerate its oxidative deterioration, especially in the presence of light. In this scenario, the filtration technology may ameliorate the oxidative stability of the oil, with positive effects on its nutritional quality and shelf life. Therefore, in this study, the oxidative stability and minor compounds of non-filtered and filtered HO (NF-HO and F-HO) were monitored over 12 weeks of storage in transparent glass bottles. F-HO showed a better hydrolytic and oxidative status than NF-HO during storage. As a result, F-HO also displayed better preservation of total MUFAs and PUFAs in the autoxidation process. Filtration consistently reduced chlorophylls, thus causing a variation in the natural color of HO. Accordingly, F-HO not only revealed an increased resistance to photooxidation but it was also suitable for storage in clear bottles within 12 weeks. F-HO predictably showed lower carotenoids, tocopherols, polyphenols, and squalene compared to NF-HO. However, filtration appeared to play a "protective role" toward these antioxidants, which had lower degradation rates in F-HO than NF-HO for 12 weeks. Interestingly, the element profile of HO was not affected by filtration and remained stable during the study period. Overall, this study may be of practical use to both producers and marketers of cold-pressed HO.